The Emotional Geography of International Students in Online Bahasa Indonesia Learning during the COVID-19 Pandemic - Susanto, Gatut; Suparmi; Rahayu, Endah Yulia (Journal of International Students, 2020)
This article reports a case study that explores the emotional geography of 25 international students from 12 countries in learning bahasa Indonesia for foreigners virtually during the COVID-19 pandemic. Grounded in a qualitative case study design, the recruited participants were interviewed about their emotional experience of learning bahasa Indonesia online. Data were garnered from the interviews, classroom observations, and students’ testimonials. They were analyzed with Hargreaves’s (2001) emotional geography theory. Findings showed that online bahasa Indonesia learning affects the emotional geography of international students. The international students experienced such positive feelings as intimacy, safety, happiness, seriousness, and successfulness. However, they also experienced such negative feelings as confusion, anxiety, and shock situated in online bahasa Indonesia learning. This indicates that international students should have positive feelings and maintain such feelings in order to succeed in online bahasa Indonesia learning.